Socio-demographic and clinical profile of mixed opioid and amphetamine type stimulant dependent subjects attending methadone maintenance therapy clinic in Kuala Terengganu, Malaysia: A preliminary report - Nur Khadijah, Muhamad Jamil; Nurul Asma, Abdullah; Ruzilawati, Abu Bakar; Imran, Ahmad (2020)
In recent years, the increasing trend of amphetamine type stimulant (ATS) use among opioid dependent was strikingly afflicted worldwide, including Malaysia.. A descriptive study was carried out to provide information of sociodemographic and clinical characteristics of mixed opioid and ATS dependent subjects undergoing the MMT program in Methadone Clinic in Kuala Terengganu in order to enhance the management related to health and social effects. A total 36 subjects who fulfilled the inclusion and exclusion criteria were recruited and interviewed. The mean (SD) age of patients was 40.98 years (SD 4.64), and the most common age of initiation was 15–20 years (42%). Most of the educational background were up to high school level (44%). Morphine and methamphetamine were the most abused substances. The majority of 83.1% used injections as their method of opioid ingestion, while 65.3% preferred chase to ingest ATS. About 30.6% of drug-dependent subjects in this study were on MMT for a 4-year duration with 63.5% of them were on methadone dosage between 45-70mg/day. Most of them demonstrated no history of arrested and conviction for drug use (63.9%) or other criminal acts nonrelated to drug abuse (94.5%). This study provide update and supportive information of socio-demographic and clinical characteristics of mixed opioid and ATS dependent subjects undergoing the MMT program that may contribute towards comprehensive management to overcome the significant surge of ATS use among opioid dependents.